SINTESIS SILIKA MCM-41 DAN UJI KAPASITAS ADSORPSI TERHADAP METILEN BIRU - ahda, Mustofa; Sutarno, Sutarno; Kunarti, Eko Sri (Universitas Ahmad Dahlan, 2013)
Synthesis of MCM-41 with hydrothermal time variation 18, 24, 36, 48 hoursusing templating agent cetiltrimetilammonium bromide (CTAB) has been done. Theresults showed that the time of hydrothermal influence the intensity and the index field(ao). Synthesis of MCM-41 with a time of hydrothermal 24 hours produce the highestintensity which indicates that MCM-41 has the best crystallinity. While testing theadsorption capacity of MCM-41 has 37,037 mg/g for adsorption of the methylene blue.